Asymmetric Macular Structural Damage Is Associated With Relative Afferent Pupillary Defects in Patients With Glaucoma - Gracitelli, Carolina Pelegrini Barbosa [UNIFESP] (2016)
PURPOSE. We examined the relationship between relative afferent pupillary defects (RAPDs) and macular structural damage measured by macular thickness and macular ganglion cell-inner plexiform layer (mGCIPL) thickness in patients with glaucoma. METHODS. A cross-sectional study was done of 106 glaucoma patients and 85 healthy individuals from the Diagnostic Innovations in Glaucoma Study. All subjects underwent standard automated perimetry (SAP) and optic nerve and macular imaging using Cirrus Spectral Domain Optical Coherence Tomography (SDOCT). Glaucoma was defined as repeatable abnormal SAP or progressive glaucomatous changes on stereo photographs. Pupil responses were assessed using an automated pupillometer, which records the magnitude of RAPD (RAPD score), with additional RAPD scores recorded for each of a series of colored stimuli (blue, red, green, and yellow). The relationship between RAPD score and intereye differences (right minus left eye) in circumpapillary retinal nerve fiber layer (cpRNFL) thickness, mGCIPL, macular thickness, and SAP mean deviation (MD), was examined using linear regression. RESULTS. There was fair correlation between RAPD score and asymmetric macular structural damage measured by intereye difference in mGCIPL thickness (R-2 = 0.285, P < 0.001). The relationship between RAPD score and intereye difference in macular thickness was weaker (R-2 = 0.167, P < 0.001). Intereye difference in cpRNFL thickness (R-2 = 0.350, P < 0.001) and SAP MD (R-2 = 0.594, P < 0.001) had stronger association with RAPD scores compared to intereye difference in mGCIPL and macular thickness. CONCLUSIONS. Objective assessment of pupillary responses using a pupillometer was associated with asymmetric macular structural damage in patients with glaucoma.